1991
DOI: 10.1530/jrf.0.0910411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of progestagen treatment on concentrations of prostaglandins and oxytocin in plasma from the posterior vena cava of post-partum beef cows

Abstract: The role of PGF-2 alpha in determining the lifespan of corpora lutea in the post-partum beef cow was investigated. In control cows (N = 5) induced to ovulate at Day 28 to 36 post partum by injection of 1000 i.u. hCG, corpora lutea had an average lifespan of only 8 days. In cows pretreated with 6 mg implants of a progestagen (norgestomet, N = 4) for 9 days, with implant removal 2 days before injection of hCG, luteal lifespan averaged 17.5 days. Concentrations of PGF-2 alpha in 9 hourly samples of plasma collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
1

Year Published

1992
1992
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 23 publications
4
45
0
1
Order By: Relevance
“…Secretion of progesterone was similar to that observed in cows during a normal oestrous cycle (Copelin et al, 1987(Copelin et al, , 1989. In other studies, pulse amplitude and basal concentrations of plasma PGF2a were increased on days 4-9 for postpartum cows having a short rather than a normal length oestrous cycle (Cooper et al, 1991), and secretion of PGF2a in vitro from endometrial tissue from cows anticipated to have short (Zollers et al, 1991b). Injection of oxytocin on day 5 of the oestrous cycle induced a release of 13,14-dihydro-15-keto prostaglandin F2a (PGFM) in cows with a short, but not normal, oestrous cycle length (Zollers et al, 1989).…”
Section: Resultssupporting
confidence: 80%
“…Secretion of progesterone was similar to that observed in cows during a normal oestrous cycle (Copelin et al, 1987(Copelin et al, , 1989. In other studies, pulse amplitude and basal concentrations of plasma PGF2a were increased on days 4-9 for postpartum cows having a short rather than a normal length oestrous cycle (Cooper et al, 1991), and secretion of PGF2a in vitro from endometrial tissue from cows anticipated to have short (Zollers et al, 1991b). Injection of oxytocin on day 5 of the oestrous cycle induced a release of 13,14-dihydro-15-keto prostaglandin F2a (PGFM) in cows with a short, but not normal, oestrous cycle length (Zollers et al, 1989).…”
Section: Resultssupporting
confidence: 80%
“…It was therefore concluded that about half of the difference in ability to maintain pregnancy between the two groups of cows was due to effects on the oocyte or embryo itself before Day 7 and the other half to a hostile uterine environment after Day 7. The apparent timing of embryo loss in this study seemed to coincide with increased PGF 2α secretion as observed by Cooper et al (1991). Moreover, in a similar experiment, there was a negative correlation between the quality of embryos on Day 6 and concentrations of PGF 2α in uterine flushings (that were higher for cows with short luteal phases; Schrick et al 1993).…”
Section: Short Duration Of the Luteal Phasesupporting
confidence: 67%
“…Pretreatment of cows 22 to 36 d postpartum with a progestogen for 9 d resulted in the formation of a CL with a normal functional lifespan in response to weaning or gonadotropin treatment (Sheffel et al 1982). Secretion of PGF 2α rose during pretreatment in the same manner as during a short luteal phase (Cooper et al 1991); therefore, if the uterus had not been previously exposed to progestogen, secretion of PGF 2α increased prematurely when the first postpartum CL began to secrete progesterone.…”
Section: Short Duration Of the Luteal Phasementioning
confidence: 99%
See 1 more Smart Citation
“…The following evidence indicates that the short luteal phase in cattle and sheep is due to a premature uterine secretion of prostaglandin F20 (PGF2a): (i) hysterectomy prevents regression of corpora lutea anticipated to have short lifespans in prepuber¬ tal ewe lambs (Keisler et al, 1983), anoestrous ewes (Southee et al, 1988) and postpartum cows (Copelin et al, 1987) oxytocin induces a release of PGF2a in cattle on day 5 of a short but not a normal luteal phase (Zollers et al, 1989); (iii) basal and oxytocin-induced secretion of prostaglandins (in vitro) from bovine endometrium is greater on day 5 of a short compared with a normal luteal phase (Zollers et al, 1991); (iv) mean con¬ centrations of PGF2a in the vena cava on days 4-9 following first postpartum oestrus are higher in cows exhibiting a short compared with a normal oestrous cycle (Cooper et al, 1991); ( ) mean concentration of 15-keto-13,14-dihydroprostaglandin F2a (PGFM; the stable metabolite of PGF2a) in plasma increases from day 3 to day 5 in ewes expected to have short oestrous cycles (Hunter et al, 1989); and (vi) active immunization of beef cows early post partum against PGF2a extends the lifespan of corpora lutea that are expected to be short-lived (Copelin et al, 1989 (Copelin et al, 1989 (Fig. 2a and b (Fig.…”
Section: Introductionmentioning
confidence: 99%